PROBLEMATIKA HUKUM KESATUAN PENGELOLAAN HUTAN DI INDONESIA - Dessy Eko Prayitno; Andi Chairil Ichsan (Jurnal Belantara, 2021)
The purpose of this research is to analyze the legal issues that cause FMUs to not work optimally in managing forests sustainably. Some of the legal issues analyzed are related to the institution, permit authority, funding, and RPHJP development. This research uses a statute approach and retrospective (ex-post) analysis by examining various laws and regulations in the forestry sector related to FMUs and its implementation. The results of this study indicate that the FMU has serious legal issues in terms of institution, permit authority, funding, and Long-Term Forest Management Plan/RPHJP development. From an institutional perspective, FMUs are at the crossroads of the authorities of the four directorates generals in the Ministry of Environment and Forestry. In terms of authority, FMUs are the spearhead of forest management at the site level, but FMUs do not have adequate authority in managing forests in their areas. Then from the funding side, FMUs are faced with a minimum budget as well as no guarantee of funding for their RPHJP. And finally, in terms of the RPHJP development, FMU faces serious challenges after the enactment of Law No. 23/2014, and laws and regulations overlapping, particularly those related to the implementation of DG Forest Planology Regulation No. P.5/2012..